The Specific Heat Capacity, Effective Thermal Conductivity, Density, and Viscosity of Coolants Containing Carboxylic Acid Functionalized Multi-Walled Carbon Nanotubes - Amiri, A.; Shanbedi, M.; AliAkbarzade, M.J. (Taylor & Francis, 2016)
Obviously, the behavior of thermophysical properties of covalently functionalized CNT-based water and -based ethylene glycol (EG) nanofluids cannot be predicted from the predicted models. We present a study of the specific heat capacity, effective thermal conductivity, density, and viscosity of coolants containing functionalized multi-walled carbon nanotubes (CNT-COOH) with carboxylic acid groups at different temperatures. After synthesizing of CNT-COOH-based water and CNT-COOH-based EG nanofluids, measurements on the prepared coolant were made at various concentrations by different experimental methods. While the thermal conductivity of both nanofluids illustrated a significant increase, the specific heat capacity of both samples showed a downward behavior with increasing temperature. Although the thermal conductivity of CNT-COOH-based water nanofluids is bigger than CNT-COOH-based EG nanofluids, CNT-COOH-based water has weaker temperature dependence than that of the CNT-COOH-based EG nanofluids. The viscosity was investigated in different shear rates and temperatures. It is noteworthy that CNT-COOH-based EG nanofluids show relatively a non-Newtonian behavior. Interestingly, specific heat capacities of both prepared nanofluids were decreased with increasing concentration. Also, the density of the CNT-COOH-based water and -based EG nanofluids increased and decreased smoothly with increasing CNT-COOH concentration and temperature, respectively.